Can AI-generated news reduce hostile media perceptions? Findings from two experiments - Huh, Estel; Kubin, Emily; von Sikorski, Christian (Frontiers in Communication, 2025)
IntroductionThe current debate regarding artificial intelligence (AI) raises the question of whether AI-generated news articles on controversial topics can reduce news consumers’ hostile media perceptions (HMP). In addition, there is a debate about people’s prior attitudes toward AI and how it influences people’s perceptions of AI-generated news articles.MethodsBased on the theoretical foundation of the MAIN model and the Hostile Media Phenomenon, we conducted two preregistered experimental studies in the United States (N = 1,197). All subjects were presented with a news article on a divisive and polarizing topic (gun regulation), but we systematically varied the supposed author of the article (human journalist, AI-generated, AI and human journalist working together).Results and DiscussionIn both studies exposure to the AI-generated news article significantly reduced participants’ HMP. However, the effect was only detected for individuals with negative and moderate prior attitudes toward AI. Individuals with positive AI attitudes did not benefit from AI-generated articles. AI-assisted news reporting showed very limited effects (only in Study 2). Furthermore, we examined if HMP predict online engagement. While Study 1 showed no effects on online engagement, Study 2 revealed that exposure to an AI-generated news article indirectly increased online engagement (intention to share a news article with friends and family). Implications for communication and journalism are discussed.